Timaviella dunensis sp. nov. from sand dunes of the Baltic Sea, Germany, and emendation of Timaviella edaphica (Elenkin) O.M. Vynogr. & Mikhailyuk (Synechococcales, Cyanobacteria) based on an integrative approach - Mikhailyuk, Tatiana; Vinogradova, Oksana; Holzinger, Andreas; Glaser, Karin; Akimov, Yuri; Karsten, Ulf (Phytotaxa, 2022)
Timaviella Sciuto & Moro is a recently established cryptic genus of cyanobacteria separated from the morphologically close Leptolyngbya due to clear differences in the 16S rRNA gene sequence and the 16S-23S ITS region secondary structure. Conducting research on biological soil crusts in coastal ecotopes of Ukraine and Germany, we repeatedly observed thin filamentous cyanobacteria morphologically corresponding to the common terrestrial species Leptolyngbya edaphica (Elenkin) Anagnostidis & Komárek. Molecular data based on 16S rRNA gene sequence comparison of the original strains of the morphospecies indicated unambiguous assignment to the genus Timaviella. Based on this finding, we proposed the new nomenclatural combination Timaviella edaphica (Elenkin) O.M. Vynogr. & Mikhailyuk in our previous publication. Deeper molecular study of the four original strains which were morphologically identified as T. edaphica based on the 16S rRNA gene concatenated with the 16S-23S ITS region and 16S-23S ITS secondary structure analysis showed that they are not identical. Three of them (isolated from biocrusts of Black Sea coast and forest path near Kyiv, Ukraine) had high similarity both in 16S rRNA (99.7–100%) and 16S-23S ITS (99.8–100%) hence actually representing T. edaphica. The strain Us-6-3 isolated from biocrusts on sand dunes of Usedom Island in the Baltic Sea, Germany, differs both from original strains of T. edaphica and all published Timaviella species in 16S rRNA gene sequence identity, as well as in sequence and structure of the 16S-23S ITS region. Here we describe Timaviella dunensis sp. nov. and give an expanded description of T. edaphica based on morphological and molecular features. A tabular review of Timaviella species with data on their phenotypic and genotypic features, ecology and distribution is included.